Creative Economic Base on Green Economic at Ecotourism Village Ramang-Ramang Maros South Celebes - Sry Wahyuni; Ade Damayanti (AJAR, 2023)
This study aims to provide an overview of the green economy-based creativeeconomy in the Ramang-Ramang Tourism Village, Maros district, South Sulawesi. Theexistence of a tourist object has an impact on people's lives in the area of the tourist object.Both from an environmental, economic, and cultural point of view. Ecotourism is a specialinterest tourism concept that combines tourism and environmental preservation as well ascommunity economic empowerment. This research was conducted using a qualitativeapproach with a case study research design with a unit of analysis of Creative Economy Actorsin the Ramang-Ramang Tourism Village, Maros Regency, South Sulawesi. The technique thatwill be used to find informants is the snowballing sampling technique. Data was collected byobservation, interview, and documentation techniques with the researcher as the instrument.The results of this study indicate that there are three sub-sectors of the creative economythat are run in the Ramang-Ramang tourist village, namely, Culinary, Kraft and PerformingArts. These three sub-sectors have experienced a lot of development and have become oneof the pillars that support the existence of the Ramang-Ramang tourism village. Apart fromencouraging the economic welfare of the community, the green economy concept applied inthe Ramang-Ramang tourist village is also an effort to preserve the environment.